Cultural Influences on Family Mealtime Routines in Mexico: Focus Group Study with Mexican Mothers - Elizabeth Villegas; Amber J. Hammons; Angela R. Wiley; Barbara H. Fiese; Margarita Teran-Garcia (MDPI AG, 2022)
Mexico's obesity rates are alarming, and experts project drastic increases in the next thirty years. There is growing interest in understanding how remote acculturation and globalization processes influence health behaviors. The present study used focus group data from a central state, San Luis Potosí, in Mexico to explore mothers' perspectives on factors that influence family mealtime routines. Thematic analysis was used to identify barriers and facilitators to healthy mealtime routines and diet within families. Twenty-one mothers participated in the focus groups; 76% were full-time stay at home mothers, the majority were low-income (65%), and fewer than half reached a high school education. Three major themes emerged: (1) mothers do most of the visible work involving mealtime routines; (2) family meals are different today, and globalization is a contributing factor; and (3) family mealtimes are shifting to weekend events. Empowering mothers to negotiate diet with family members to build healthy routines, navigate challenges due to changing environments, and set family boundaries around technology use during mealtimes should be taken into consideration when promoting healthy behaviors with Mexican families.